Exploring Survivor Experiences on Social Media in the #MeToo Era: Clinical Recommendations for Addressing Impacts on Mental Health and Relationships. Issue 21 (November 2022) - PettyJohn, Morgan E.; Anderson, Grace; McCauley, Heather L.
Since the inception of the viral #MeToo Movement in 2017, news coverage of sexual assault incidents and related public discourse have become much more prevalent on social media platforms. While this hashtag activism has prompted important social discourse, little is known about how exposure to this type of trauma-related content affects survivors of sexual violence navigating these online spaces. To explore this phenomenon, we conducted in-depth, semi-structured interviews with young adult women survivors of sexual assault who regularly use social media (e.g., Facebook and Twitter). Participants were asked to reflect on sexual assault–related content (i.e., news stories and related public discourse) which they have observed on social media platforms. Thematic analysis of the qualitative data found survivors described (1) negative changes to their mental health and relationships in the face of these exposures, (2) certain types of content (e.g., rape culture narratives) which were particularly distressing to them, (3) how they coped with distress tied to this exposure, and (4) recommendations for clinicians on how to help survivors navigate social media in a healthier way. The present study is a first step toward understanding the impact of online social movements on trauma survivors and provides concrete clinical recommendations for therapists working with sexual assault survivors in this unique post-#MeToo context.